2023
DOI: 10.1021/acsami.3c02087
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Mirror-Assisted and Concave Pyramid-Shaped Solar–Thermal Steam Generator for Highly Efficient and Stable Water Evaporation and Brine Desalination

Abstract: Although significant advances have been achieved in developing solar-driven water evaporators for seawater desalination, there is still room for simultaneously enhancing water evaporation efficiency, salt resistance, and utilization of solar energy. Herein, for the first time, we demonstrate a highly efficient three-dimensional (3D) mirror-assisted and concave pyramid-shaped solar–thermal water evaporation system for high-yield and long-term desalination of seawater and brine water, which consists of a 3D conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The effectiveness of this work is demonstrated by the fact that the performance of the TIE with natural convection support is ∼32% greater than that of 3D evaporators with side evaporation and no forced convection. 32–37…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of this work is demonstrated by the fact that the performance of the TIE with natural convection support is ∼32% greater than that of 3D evaporators with side evaporation and no forced convection. 32–37…”
Section: Resultsmentioning
confidence: 99%
“…In general, the performance of a solar evaporator is related to two factors: the properties of the photothermal material used and the structural design of the evaporator. Photothermal materials play an essential role in interfacial solar evaporation, which can convert the absorbed sunlight into heat for vapor generation at the air–water interface. , Common photothermal materials include carbon materials, metal plasma, , semiconductors, and organic polymers. As a conjugated polymer, polypyrrole (PPy) has unique advantages such as outstanding photothermal properties, high stability, and low cost and is a promising photothermal material for solar evaporation applications. For example, Fan et al demonstrated that the light absorption of cellulose papers can be significantly increased from 48% to 95.5% when they are coated with PPy . Yu et al also showed that a hierarchically nanostructured poly­(vinyl alcohol) gel containing PPy as the photothermal additive can achieve an impressive solar energy harvesting efficiency of over 95% .…”
Section: Introductionmentioning
confidence: 99%